Chapter Roman Law in the regnum Italiae under the Emperor Lothar I (817‒855): Epitomes, Manuscripts, and Carolingian Legislation - Esders, Stefan (Reti Medievali E-Book, 2022)
"Roman law" could mean very different things in the Carolingian period, and refers to a great variety of legal texts. This becomes particularly visible from the abbreviated versions of Roman law that were produced and circulated since the 6th century. The paper contrasts the so-called Epitome Aegidii, a Gallic compilation based on the Breviary of the Visigothic King Alaric II, with the so-called Epitome Iuliani, a short version of the novels of the Emperor Justinian, as both abbreviated compilations were used in the regnum Italiae under the Frankish Emperor Lothar I for legislation and legal practice. Both compilations attest to different aspects of the Roman legal tradition, and to the divergent purposes of the Frankish rulers when trying to make use of Roman law. Surprisingly, we also find elements of Ostrogothic law incorporated into what was perceived of in Carolingian Italy as the manifold resources of the Roman legal tradition.